Making DEEP Sense of Lifestyle Risk and Resilience - Kempermann, Gerd (Frontiers in Aging Neuroscience, 2019)
To effectively promote life-long health and resilience against — for example — neurodegenerative diseases, evidence-based recommendations must acknowledge the complex multidimensionality not only of the diseases but also of personal lifestyle. In a straightforward descriptive and heuristic framework, 50+ potential lifestyle factors cluster around diet (D), education (E), exercise (E) and purpose (P), unveiling their many relationships across domains and scales. The resulting systematics and its visualization might be a small but helpful step towards the development of more comprehensive, interdisciplinary models of lifestyle-dependent risk and resilience and a means to explain the opportunities and limitations of preventive measures to the public and other stakeholders. Most importantly, this perspective onto the subject implies that not all lifestyle factors are created equal but that there is a hierarchy of values and needs that influences the success of life-style based interventions.